The single motherhood penalty as a gender penalty - Sophie Moullin; Susan Harkness (Luxembourg Income Study (LIS), 2021)
Recent analysis has suggested that poverty rates, and their variation across rich countries, is driven much less by the prevalence of certain risks than by the poverty penaltyattached to the risks. Focusing on single motherhood as a poverty risk, it is claimed the penalty attached to it is specific to the United States. This claim, we show, relies on models that condition on the major mechanisms through which poverty risks are heightened: the risk of non-employment, and of having only a single earner, in the household. Removing these conditions, we find that the poverty penalties associated with single motherhood accounts to a similar degree to the prevalences of single motherhood for variation in poverty rates in rich countries. The penalty averages 16% and is significant in 27 out of 28 countries. At nearly 26%, the penalty in the United States is comparatively high, but not exceptionally so, with 9 out of 28 countries having penalties over 20%. Any comparative analysis of poverty or inequality, we argue, must recognize the joint role of work, welfare and family institutions. In all but the Scandinavian nations, these institutions remain gendered.
Keywords: 330; Alleinerziehende; Mütter; Haushaltseinkommen; Armut; Welt